Comparison of requirements for environmental protection and a model for evaluating contaminated sites in Lithuania - Vasarevičius, Saulius; Kadūnas, Kęstutis; Baltrėnaitė, Edita (Technological and Economic Development of Economy, 2013)
This work is aimed at addressing attention to the situation of contaminated sites and emphasizing importance and need for their rehabilitation. The study presents the experience gained by European countries evaluating contaminated sites and rehabilitation framework. A model of assessing contaminated sites in Lithuania consisting of two main stages – preliminary and detailed investigation has been developed. The first one is used for collecting preliminary information on the contaminated site and for evaluating the need for detailed analysis. The second is subjected to a comprehensive risk assessment of the site shifting focus on the environment and human health. The model for evaluating contaminated sites involves organic chemical materials and metals. Risk assessment depends on the sensitivity of a site to contamination. Equations for establishing the level of contamination involve the content of soil organic matter and clay. Correction coefficients used for calculating the level of contamination have been based on statistical analysis and experience gained by the EU countries.